2008
DOI: 10.1159/000151509
|View full text |Cite
|
Sign up to set email alerts
|

Familial Aggregation of Skin Sensitization to Aeroallergens in a Rural Area in China

Abstract: Background: The prevalence of allergic sensitization has increased all over the world during last years and allergic sensitization may be related to genetic or environmental factors or to both. The objective of this study was to estimate the prevalence rates of allergic sensitization and assess the familial aggregation of allergic sensitization to aeroallergens in asthma index families. Methods: The skin prick test (SPT) reactivity to 8 aeroallergens and the SPT reactivity-related risk factors were evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
3
3
0
Order By: Relevance
“…Unlike asthma, allergic rhinitis was consistently associated with sensitization to mites and cockroach in our study, a finding in line with other studies performed in South-East Asia [2,4,20,31]. The associations were similar for all studied mite species, although co-sensitization between species was common as previously discussed.…”
Section: Discussionsupporting
confidence: 93%
“…Unlike asthma, allergic rhinitis was consistently associated with sensitization to mites and cockroach in our study, a finding in line with other studies performed in South-East Asia [2,4,20,31]. The associations were similar for all studied mite species, although co-sensitization between species was common as previously discussed.…”
Section: Discussionsupporting
confidence: 93%
“…The most common allergen was HDM, which is consistent with the finding of previous studies in Korea (1314), Chinese, and Turkey (2223). However, the present study indicated a geographical difference in the sensitization rate to HMD allergens, although it was within Korea.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the prevalence of aeroallergen sensitization in elementary schoolchildren was 41.1%, while the prevalence in middle schoolchildren was 55.0%. The prevalence shows a similar level to results in other countries from 39% to 58%, although the dominating allergen is different in various geographic areas (16-18). In addition, our rates are similar to those found in other studies of sensitization in general schoolchildren in some restricted areas of Korea (6, 7).…”
Section: Discussionsupporting
confidence: 82%
“…Those results are consistent with other data reported in Korea (6, 12, 19). Some studies in China and Turkey have reported that HDM was the most common allergen (18, 20), while those in Estonia and Europe have pointed to grasses and cockroach as dominating allergens (1, 14, 21). Tyr p , which is known to be a storage mite, was the dominating sensitizer in Gangwon and Jeju-do.…”
Section: Discussionmentioning
confidence: 99%